Perbedaan Aspirasi Karir Antara Wanita yang Sudah Menikah dan yang Belum Menikah Pegawai Negeri Sipil - Retno Setyowati; Bagus Riyono (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2003)
This study examined difference in career aspiration between married and single women who work for government offices. Subjects of study were government employee at Pemda Kulon Progo with a total number of 120 person; 84 of them were married with working husband and 36 were single working women. Data were collected through questionnaire consisting Career Aspiration Scale (Wisnuwardhani 1998) and demographic data questionnaire. The data were analyzed with t-test for independent samples and product moment correlation analysis. The result shows that there is no significant difference on career aspiration between married-women and single-women working for government offices (t=1,379; p>0,05). Other results reveal that level of education influences the magnitude of career aspiration (r=0,269 ; pKey Words : Career aspiration, Married and Single women.